Implementation of Problem Solving Method in Improving Learning Outcomes of Fourth Grade Students at MI Al Falah Pagu Wates Kediri - Khotimah, Husnul; Priyanti, Lestari Dwi (Indonesian Journal of Multidisciplinary Educational Research, 2023)
The purpose of this research is to investigate the implementation of the Problem Solving method that has proven to improve the learning outcomes of fourth-grade students at MI Al Falah Pagu Wates Kediri in the academic year 2022/2023, specifically in Social Sciences subject. The research design consists of four stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The research subjects were 25 fourth-grade students at MI Al Falah Pagu Wates Kediri, comprising 15 male students and 10 female students. Data collection techniques included observation, interviews, tests, and field notes. The data analysis technique used the average of student activities and the final test scores. The results showed that the implementation of the Problem Solving method in the Social Sciences subject could improve the fourth-grade students' learning outcomes at MI Al Falah Pagu Wates Kediri. This was shown in the increase in the percentage of student learning activities from 55.2% to 82% and had an impact on the average learning outcomes of students, which increased from 73.65 to 83.4.